Modulation of Immune Responses by Platelet-Derived ADAM10 - Maurer, Stefanie; Kopp, Hans-Georg; Salih, Helmut R.; Kropp, Korbinian N. (Frontiers in Immunology, 2020)
Platelets have a crucial function in maintaining hemostasis. However, beyond their role in coagulation and thrombus formation, platelets have been implicated to affect various pathophysiological conditions such as infectious diseases, autoimmune disorders and cancer. It is well established that platelets aid local cancer growth by providing growth factors or contributing to cancer angiogenesis. In addition, they promote metastasis, among others by facilitation of tumor cell-extravasation and epithelial-to-mesenchymal transition as well as protecting metastasizing cancer cells from immunosurveillance. A variety of membrane-bound and soluble platelet-derived factors are involved in these processes, and many aspects of platelet biology in both health and disease are regulated by platelet-associated metalloproteinases and their inhibitors. Platelets synthesize (i) members of the matrix metalloproteinase (MMP) family and also inhibitors of MMPs such as members of the “tissue inhibitor of metalloproteinases” (TIMP) family as well as (ii) members of the “a disintegrin and metalloproteinase” (ADAM) family including ADAM10. Notably, platelet-associated metalloproteinase activity not only influences functions of platelets themselves: platelets can also induce expression and/or release of metalloproteinases e.g. in leukocytes or cancer cells, and ADAMs are emerging as important components by which platelets directly affect other cell types and function. This review outlines the function of metalloproteinases in platelet biology with a focus on ADAM10 and discusses the role of platelet-derived metalloproteinases in the interaction of platelets with components of the immune system and/or cancer cells.